Ergonomics how to design for ease and efficiency - Kroemer, K. H. E (Prentice-Hall international series in industrial and systems engineering., 1994)
Kroemer focuses on human interaction with work tasks and technology and discusses ways to amplify human capabilities, utilize human abilities and facilitate human efficiency. The book is divided into four topical areas: Anatomical and Mechanical Structure of the Human Body; How the Body does its Work; How the Mind Deals with the Environment; and How the Body Interacts with the Environment.